Cockroaches (Blattaria) of Ecuador—checklist and history of research - Vidlička, Ľubomír (Zootaxa, 2013)
Cockroaches are an understudied group and the total number of described taxa increases every year. The last checklist of Ecuador species was published in 1926. The main aim of this study was to complete a new checklist of cockroach species recorded in Ecuador supplemented with a research history of cockroaches (Blattaria) on the territory of continental Ecuador. In addition, the checklist contains comments on Ecuadorian faunistic records, including the Galápagos Islands. A total of 114 species (105 in continental Ecuador and 18 in Galápagos Islands) belonging to 6 families and 44 genera are listed. Forty species (38.1 %) occur solely in continental Ecuador and five (27.8 %) are endemic on Galápagos Islands. The results indicate that further research on the cockroach fauna of Ecuador as well as determination of museum collections from this territory is needed